Germinação e vigor de sementes de senna spectabilis (dc) h. S. Irwin & barneby sob estresse hídrico - Brito, Ana Claudia de (Universidade Federal Rural do Semi-Árido, 2017)
Knowledge about the performance of seed germination and vigor in water stress conditions is important to help in choosing species more adapted to these conditions, contributing to management strategies. The aim of this study was to evaluate the germination and vigor of Senna spectabilis seeds under conditions of water stress at two temperatures. The seeds were purchased from the Ecology and Environmental Monitoring Center and the São Francisco Integration Project. The experimental design was completely randomized, with treatments distributed in a factorial scheme, corresponding to four stress levels simulated with polyethylene glycol (PEG 6000) (0.0, -0.2, -0.4 and -0.6 MPa) and two temperatures (25 and 30 °C), with four replicates of 25 seeds for each treatment. For this purpose, germination test on paper towel substrate (Germitest®), moistened with PEG 6000 solutions in the mentioned potentials, was installed under photoperiod of 8 hours of light. The analyzed variables were germination, germination speed index, shoot and root length, shoot dry weight and seedling roots. The germination and vigor of S. spectabilis silts are drastically compromised from water potentials lower than -0.4 MPa, the effect of water stress being less intense at 30 °C.
Monografia
Keywords: Fabaceae; Canafístula; PEG; Restrição hídrica; Fabaceae; Canafístula; PEG; Water restriction; CIENCIAS AGRARIAS::AGRONOMIA